Changes to Venous Flow Coupler Signal during DIEP Flap Inset Can Be Predictive of Poor Clinical Outcomes in Autologous Breast Reconstruction - Colakoglu, Salih; Johnson, Ariel; Anderson, Jaclyn; Mathes, David Woodbridge; Chong, Tae Woon (Journal of Reconstructive Microsurgery, 2020)
Background Venous flow couplers are typically used to monitor free flaps during the postoperative period, with a continuous venous signal available immediately after completion of the anastomosis. Intraoperative loss of the coupler signal is not uncommon and may require adjustments in free flap inset and even flap thickness to get the venous signal to return. The effects of intraoperative coupler signal loss and the role of this technology on flap outcomes have not been evaluated. We hypothesized that the use of intraoperative coupler can be protective of both early and late flap complications by preventing unfavorable flap insets.Patients and Methods All patients who underwent free flap breast reconstruction between January 2018 and June 2019 by single microsurgery team were included. Flap inset and inset changes based on flow coupler signal problems were reviewed in the procedure notes. Patient demographics data and clinical outcomes were analyzed with comprehensive chart review.Results Forty-four consecutive patients with 69 free flaps were identified. There were no significant differences in patient characteristics or venous coupler size used in venous anastomosis. Although the number of operating room take backs for venous insufficiency was not significantly different between two groups, the free flaps with inset change had significantly higher complications that required later surgical intervention (p = 0.0464).Conclusion Surgeons should be aware that intraoperative coupler signal loss can be associated with poor clinical outcomes postoperatively and these flaps may require more perfusion imaging, flap debulking, or even additional venous anastomosis.
Keywords: breast reconstruction; deep inferior epigastric perforator flap; venous coupler; flap inset; microsurgery